EFFECTS OF PHOSPHORUS ADDITIONS ON LEAD AND MERCURIUM BIOAVAILABILITIES IN A CONTAMINATED SOIL - Armelin, M. J. A.; Trevizam, A. R.; Silva, M. L. S.; Saiki, M.; Maihara, V. A. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The soils enriched with elements potentially toxic (EPT) have limited use for agricultural purposes. In this case, the corresponding site should be isolated and then procedures for decontamination or stabilization of EPT in the soils must be applied. The objective of this study was to evaluate the influence of adding different rates of phosphate on the bioavailability of mercury (Hg) and lead (Pb) in a contaminated soil, using lettuce grown on this soil. For this, different phosphorus rates were used to control bioavailability of Hg and Pb, in lettuce plants. The element concentrations were analyzed by instrumental neutron activation analysis (INAA), and the results were compared to control treatment to verify the reduction of absorption of Hg and Pb. The Hg concentration in shoots decreased with the application of 250 mg kg-1 of P and Pb with the application of 250 to 1000 mg kg-1 of P. The accumulation of Hg and Pb in shoots of lettuce increased as a function of P demonstrating the inefficiency of application of P in the absorption of these elements.